Artificial Insemination in Sheep with Fresh Diluted Semen: Comparison Between Two Different Semen Extenders and Management Protocols - A. Madrigali; A. Rota; D. Panzani; S. Castellani; M. Shawahina; A. Hassan; F. Di Iacovo; C. Rossignoli; F. Camillo (Faculty of Animal Science, Bogor Agricultural University, 2021)
Timed artificial insemination (TAI) is a very important tool for reproductive programs in small ruminants, providing synchronized inseminations and more efficient use of superior males. The objectives of this study were to investigate the viability of different breeding protocols under sub-optimal conditions and out of the breeding season, and to compare the outcome of TAI in sheep with two different semen extenders. Ewes (n=575) were subjected to estrous synchronization by intravaginal sponges containing 30 mg of medroxyprogesterone acetate and PMSG. Ewes were divided into 5 groups according to the semen extender employed and to the breeding protocol: 1) egg yolk citrate AI reinforced by ram (EYC-RR); 2) Andromed AI reinforced by ram (AND-RR), where rams joined the flocks 3 hours after AI; 3) egg yolk citrate AI without ram exposition (EYC); 4) Andromed AI without ram exposition (AND). In all these groups vaginal AIs were performed 56±2 hours from sponge removal and PMSG injection; 5) natural mating (RAM) where rams were introduced 48 hours following sponge removal and PMSG injection. Pregnancy rate, parturition rate, and prolificacy were significantly higher (p<0.05) in the EYC-RR and AND-RR groups than in the EYC and AND groups. The lambing rate was not different between groups. No statistical differences were observed between breeding farms or inseminating rams. This study showed that TAI with fresh semen diluted either with egg yolk citrate or with AndroMed could be an effective and feasible tool to increase lamb production and improve genetic merits of the sheep population out of the breeding season.